(untitled) (Revista Tempo e Argumento, 2017)
This article discusses the greater presence of Portuguese colonialism in the Angolan countryside in the first half of the 20th century and the resistance to it. To do this, we follow a part of the life of the politician Adriano João Sebastião from his birth, in 1923, to his arrest, in 1960, through the analysis of his memoir book Dos campos de algodão aos dias de hoje [From the cotton fields to the present day], published in 1993. Thus, we aim to grasp how Portuguese colonialism affected the daily life of an Angolan man. Keywords: Angola; Colonization; Resistance; Adriano Sebastião; Memoirs.